Designing the collective non-local responses of metasurfaces - James R. Capers (Nature Portfolio, 2021)
Mapping the response required to obtain the desired output field from a metamaterial for a given input remains challenging due to the complexity of scattering processes. Here, a semi-analytical model for the design of aperiodic metasurfaces is presented alongside numerical examples.